Ethnozoological insights from Nepal: Vertebrate diversity in ethnomedicine - Regmi, Krishika; Karki, Apekchya; Dahal, Krishnaa; Gautam, Deepak (Nepal Journal of Environmental Science, 2025)
This study provides a review of the ethnozoological knowledge and zootherapeutic practices among the diverse ethnic communities of Nepal, noting the cultural, medicinal, conservation significance of animal- based remedies. Traditional healing systems across Nepal rely on fauna and their derivatives hence forming an important component of indigenous healthcare. Relevant literature was reviewed using PubMed, Scopus, ScienceDirect, ResearchGate and Google Scholar using key terms like “Ethno-zoological study”, “medicinal animal”, “traditional medicine”, “traditional medicine practitioner”, “Nepal”. From a total of 100 articles, 27 articles representing 20 ethnic groups were selected. In total, 97 species of vertebrates belonging to 48 families and 29 orders were identified for treating 85 distinct ailments, most associated with musculoskeletal, digestive, and reproductive disorders. The species Canis aureus, Columba livia, and Axis axis were most frequently cited, with meat, fat, and bile being the predominant animal parts utilized. Notably, 28 species were classified as globally threatened, highlighting the tension between traditional medicine and biodiversity conservation. This review aims to highlight Nepal's rich bio-cultural diversity and the role of zootherapy in primary healthcare, while identifying critical knowledge gaps in underrepresented ethnic groups. Interdisciplinary approaches involving ethnobiology, pharmacology, toxicology and conservation science are needed to validate therapeutic claims and ensure public health safety and promote sustainable management of faunal resources.